Promoting Muslim Youth Activism to Adapt Modernism Challenges - Deri Supriatna; Cicin Kuraesin; Erni Haryanti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The study is aimed to explore the challenges faced by the Muslim community today, particularly the issues of ideological and societal fragmentation in the modern era. The context of rising fundamentalism and a gradual drift from the core principles of Aqidah and Sharia. It examines the historical and ideological foundations that have shaped the perception of Islam, often linked to terrorism in global discourse, and investigates how these narratives affect unity among Muslims. The paper examines how these challenges have contributed to internal fragmentation within the ummah and the decline in religious practice among the younger generation. By focusing on the critical role of mosques as centres of both worship and community dialogue, this study argues that a revival of Islamic values can be achieved through a conscious effort to bring the youth back to the mosque. A qualitative study was conducted through a purposive sampling technique analyzed by interpretive phenomenological analysis of an interview with an Islamic scholar, Tiar Anwar Bachtiar. This study delves into themes of Aqidah (faith), unity, and community engagement, proposing practical steps for enhancing cohesion among Muslims and countering divisive narratives. The findings suggest that strengthening Aqidah through education and community interaction within mosques is essential for addressing the root causes of contemporary issues in the Muslim world. Ultimately, this paper advocates for a community-centred approach that fosters unity and spiritual rejuvenation as solutions to the pressing challenges of modernity.